Increasing Returns to Schooling by Ability? A Comparison Between the US and Sweden - Martin Nordin; Dan-Olof Rooth (Lund University, School of Economics and Management, Department of Economics, 2011)
This study uses US survey data (NLSY) and Swedish register data to estimate the relationship between returns to schooling and ability for each country separately. A significant and positive relationship is found for Sweden but not for the US. The purpose is to propose an explanation for why such differences might occur. While many studies have focused on whether credit constraints result in inefficiencies in the schooling market, this study answers the opposite question: whether weak credit constraints lead to inefficiencies, in other words in an overuse of the schooling system. It is argued argue that the US schooling system more effectively sorts out education investments with a low rate of return to schooling than the Swedish schooling system. Therefore, an imperfect allocation of individuals going to higher education in Sweden makes a relationship between returns to schooling and ability observable in Sweden but not in the US. Since the relationship between returns to schooling and ability is the same when the schooling systems of the two countries is similar, that is at lower levels of education, it is indicative of the fact that this explanation may be correct. Of course, the empirical findings in this study are not convincing evidence on their own, but the findings suggest and agree with such an explanation.
Keywords: I21; J24; 330; Cognitive ability; return to schooling; credit constraints